The Role of Tax Audits in Enhancing Regional Taxpayer Compliance - Dito Aditia Darma Nst; Irwanndri zandroto; Viktor D J Buulolo; Azun frinaldi meha; Nur Aisyah (Yayasan Multidimensi Kreatif, 2026)
Local taxpayer compliance is one of the key factors in achieving sustainable growth in regional tax revenues. However, the level of taxpayer compliance continues to face various challenges, including low tax awareness, limited supervision, and weak enforcement of local tax regulations. Tax audits function as a supervisory instrument aimed at ensuring that taxpayers comply with the prevailing regional tax laws and regulations. This study aims to analyze the role of tax audits in enhancing local taxpayer compliance and to identify factors that influence the effectiveness of tax audit implementation. The research employs a quantitative approach using a survey method, in which data are collected through questionnaires distributed to local taxpayers and regional tax administration officials. The collected data are analyzed using descriptive and inferential statistical techniques to examine the relationship between tax audit implementation and the level of taxpayer compliance. The expected findings indicate that tax audits play a positive and significant role in improving local taxpayer compliance, both in terms of formal and material compliance. Furthermore, this study is expected to provide recommendations for local governments to improve the quality of tax audit implementation as an effort to optimize regional tax revenues and strengthen transparent and accountable local tax governance.